2016
DOI: 10.1038/srep31294
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA capping enzyme of Saccharomyces cerevisiae has dual specificity to interact with CTD of RNA Polymerase II

Abstract: RNA Polymerase II (RNAPII) uniquely possesses an extended carboxy terminal domain (CTD) on its largest subunit, Rpb1, comprising a repetitive Tyr1Ser2Pro3Thr4 Ser5Pro6Ser7 motif with potential phosphorylation sites. The phosphorylation of the CTD serves as a signal for the binding of various transcription regulators for mRNA biogenesis including the mRNA capping complex. In eukaryotes, the 5 prime capping of the nascent transcript is the first detectable mRNA processing event, and is crucial for the productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Ser 5 -phosphorylated Pol II has been shown to co-purify with the capping machinery and TFIIH kinase [39]. Recent research has shown that Ser7 phosphorylation is also important for capping: it is necessary for GT Ceg1 association with Pol II in yeast [40].…”
Section: Capping Machinery Functioning Depends On Transcriptionmentioning
confidence: 99%
“…Ser 5 -phosphorylated Pol II has been shown to co-purify with the capping machinery and TFIIH kinase [39]. Recent research has shown that Ser7 phosphorylation is also important for capping: it is necessary for GT Ceg1 association with Pol II in yeast [40].…”
Section: Capping Machinery Functioning Depends On Transcriptionmentioning
confidence: 99%
“…The E. coli (BL21-DE3) was transformed with the expression construct. The protein was expressed and purified using Ni-NTA column as described somewhere [18,19]. Further purification was done using Superdex TM 75, 10/300GL column on AKTA FPLC (GE Healthcare) pre-calibrated with standard molecular weight markers.…”
Section: Cloning Expression and Purification Of Sus1mentioning
confidence: 99%
“…Both the novel CDS2 and CDS-Y2 sites are also observed at the same positions in the C. albicans cocrystal structure ( Figures 3A and 8A). In addition, CDS2 residues have been shown to be essential for CTD binding to the S. cerevisiae CE GTase (80). Sequence analysis comparing animal and yeast species shows that the core residues of both CDS2 and CDS-Y2 are functionally conserved across animals and yeasts ( Figure 8B).…”
Section: The Novel Phosphoserine Pocket Cds2 Is Essential For Gtasementioning
confidence: 99%